Dynamic sensitivity of ATP-sensitive K(+) channels to ATP. - Loussouarn, G; Pike, L; Ashcroft, F; Makhina, E; Nichols, C (2001)
ATP and MgADP regulate K(ATP) channel activity and hence potentially couple cellular metabolism to membrane electrical activity in various cell types. Using recombinant K(ATP) channels that lack sensitivity to MgADP, expressed in COSm6 cells, we demonstrate that similar on-cell activity can be observed with widely varying apparent submembrane [ATP] ([ATP](sub)). Metabolic inhibition leads to a biphasic change in the channel activity; activity first increases, presumably in response to a fast decrease in [ATP](sub), and then declines. The secondary decrease in channel activity reflects a marked increase in ATP sensitivity and is correlated with a fall in polyphosphoinositides (PPIs), including phosphatidylinositol 4,5-bisphosphate, probed using equilibrium labeling of cells with [(3)H]myo-inositol. Both ATP sensitivity and PPIs rapidly recover following removal of metabolic inhibition, and in both cases recovery is blocked by wortmannin. These data are consistent with metabolism having a dual effect on K(ATP) channel activity: rapid activation of channels because of relief of ATP inhibition and much slower reduction of channel activity mediated by a fall in PPIs. These two mechanisms constitute a feedback system that will tend to render K(ATP) channel activity transiently responsive to a change in [ATP](sub) over a wide range of steady state concentrations.